Aplikasi Sistem Manajemen Parkir Berbasis Website Di Universitas Wiraraja Madura - Ferly Fajar Hadianto; Ahmad Suwandi (Universitas Dr. Soetomo, 2024)
Parking is a place for someone to leave their vehicle when they have arrived at their destination. This is done so that the rider can comfortably carry out their activities. However, there are still many public places that only provide parking spaces without managing them properly, such as at Wiraraja Madura University. Therefore, the purpose of this research is to create a Website-Based Parking Management System at Wiraraja University, Madura. Parking Management System is a method used by organizations to manage parking in order to provide comfort to drivers. With the Parking Management System will make it easier for motorists and officers to get a parking space. The method used in this research is descriptive qualitative method. Qualitative methods are used to obtain descriptive data in the form of words and pictures. Data collection techniques used are observation, interviews and documentation. This thesis research aims to create a